Diet, physical activity, and health-related outcomes of endometrial cancer survivors in a behavioral lifestyle program: the Diet and Exercise in Uterine Cancer Survivors (DEUS) parallel randomized controlled pilot trial. Issue 3 (March 2019) - Koutoukidis, Dimitrios A; Beeken, Rebecca J; Manchanda, Ranjit; Burnell, Matthew; Ziauddeen, Nida; Michalopoulou, Moscho; Knobf, M Tish; Lanceley, Anne
Abstract : Objectives: To explore the effectiveness of a theory-based behavioral lifestyle intervention on health behaviors and quality of life in endometrial cancer survivors.' Methods: This was a secondary analysis of a randomized controlled pilot trial conducted in two UK hospitals enrolling disease-free stage I-IVA endometrial cancer survivors. Participants were allocated to an 8-week group-based healthy eating and physical activity intervention or usual care using 1:1 minimization. Participants were followed up at 8 and 24 weeks, with the 8-week assessment being blinded. Diet, physical activity, and quality of life were measured with the Alternative Healthy Eating Index 2010, Stanford 7-Day Physical Activity Recall, and the EORTC Quality of life Questionnaire Core 30, respectively. We analyzed all eligible participants using the intention-to-treat approach in complete cases, adjusting for baseline values, body mass index, and age. Results: We enrolled 60 of the 296 potentially eligible endometrial cancer survivors (May - December 2015). Fifty-four eligible participants were randomized to the intervention (n=29) or usual care (n=31), and 49 had complete follow-up data (n=24 in the intervention and n= 25 in usual care). Intervention adherence was 77%. At 8 weeks, participants in the intervention improved their diet compared to usual care (difference in Alternative Healthy Eating Index 2010 score 7.5 (95% CI: 0.1 to 14.9), P=0.046) but not their physical activity (0.1 metabolic equivalent-h/day 95% CI: (-1.6 to 1.8), P=0.879), or global quality of life score (5.0 (95% CI: -3.4 to 13.3), P=0.236). Global quality of life improved in intervention participants at 24 weeks (difference 8.9 (95% CI: 0.9 to 16.8), P=0.029). No intervention-related adverse events were reported. Conclusions: The potential effectiveness of the intervention appeared promising. A future fully-powered study is needed to confirm these findings. Trial registration number: NCT02433080.